The Impact of Working From Home on The Civil Servant Administration Performance During COVID-19 Pandemic - Suci Hati; Heri Sapari Kahpi; Uli Wildan Nuryanto; Joni Prihatin; Tubagus Iwan Ridwan (PT Mattawang Mediatama Solution, 2022)
The pandemic caused by Coronavirus 2019 (Covid-19) which originated in Wuhan, China has spread rapidly to all countries around the world including Indonesia. Various methods are used to maintain safety and prevent the spread of virus getting faster, one of methods by implementing the work from home for the civil servant administration. Therefore, this research investigates the impact of working from home to the performance of civil servant administration in Indonesia. The employees who have the possibility to work from home, have a high degree of autonomy in scheduling their work and thus considered to have higher intrinsic motivation. Thereby, the research hypothesis between working from home can positively impact on employee performance of the civil servant administration at Banten Province. This study uses quantitative methods, the data in this study used by an online questionnaire of 72 civil servant administration in Banten Province. The analysis tool using structural equation modeling (SEM) PLS. Research variable divided become three variables, the work from home as predictor for the performance of civil servant administration, while the Covid-19 pandemic as the moderator variable. The empirical results shows that working from home has a significant positive effect on performance of civil servant administration. Meanwhile, Covid-19 Pandemic as a moderating variable will be weakens the relationship between work form home (WFH) on the performance of civil servant administration.